IDENTIFIKASI MIKORIZA ANGGREK Spathoglottis plicata Blume. DAN Phalaenopsis amabilis L. IDENTIFICATION OF ORCHID MYCORRHIZA OF Spathoglottis plicata Blume. AND Phalaenopsis amabilis L. - Ningsih, Rita; ., Dinarni; Febrianti, Dwi (Jurnal BioWallacea, 2014)
Isolation and identification of mycorrhiza fungal that associated with Spathoglottis plicata Blumeand Phalaenopsis amabilis L. orchid root have be done. The descriptive research consist of threesteps that were isolation, purification and identification. Slice of roots were inoculated on PotatoDextro Agar (PDA) media for 2 â 5 days. The fungal colony were purified then identified basedon colony and morphology characters. The observed parameter were fungal colony, hypha andspore type. The result showed that there were 3 isolate found from root of terrestrial orchidSpathoglottis plicata Blume i.e SA1.1 was Chaetoium belonging to Ascomycetes class; SA2.2was Beltrania belonging to Ascomycetes class too and SA2.3 was Rhizoctonia belonging toDeuteromycetes class. Meanwhile the identification result of mycorrhiza fungal from root ofepiphytic orchid Phalaenopsis amabilis L. showed that 2 isolate i.e PA1.2 and PA1.3 both of themRhizoctonia belonging to Deuteromycetes class.Keywords : orchid mycorrhiza, Spathoglottis plicata Blume, Phalaenopsis amabilis L., orchid root